Studi Literatur: Fungsi dan Kualifikasi Guru sebagai Penopang Keberhasilan Pendidikan - Rezkiyanto Taruq Allo; Evelin Azura Soisong; Achmad Muhtadin; Ikmawati Ikmawati (International Forum of Researchers and Lecturers, 2026)
Education has a crucial role in improving the quality of human resources and shaping national character. The success of the education system depends greatly on the effectiveness of the teacher's role as the main implementer of learning who functions as an educator, guide, motivator and facilitator. This research aims to examine the functions and qualifications of teachers as support for educational success through the literature study method (library research) by analyzing various sources of scientific journals, books and relevant official documents. The analysis technique used is qualitative descriptive analysis to interpret the data systematically. The results of the study show that the teacher's function includes integrated professional, humanitarian and societal dimensions. Professionally, teachers are responsible for designing, implementing and evaluating learning. Academic qualifications and mastery of four main competencies—pedagogical, professional, social, and personality—are vital indicators in determining the quality of education. However, implementation in the field still faces challenges such as gaps in mastery of information technology (ICT) and bureaucratic obstacles in the certification process. This research concludes that improving teacher quality through continuous education and effective policies is very necessary to create adaptive and competitive learning in the digital era